PENGARUH MOTIVASI DIRI, LINGKUNGAN KELUARGA, EKSPETASI PENDAPATAN DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA AKUNTANSI - Wardan, Teresia Novianti; Wirasedana, I Wayan Pradnyantha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024, 2024)
The imbalance in the number of jobs with job seekers causes high unemployment. One of the ways to overcome unemployment is through entrepreneurship. This study aims to determine the effect of self-motivation, family environment, income expectations, and entrepreneurship education on the entrepreneurial interest of students of the Accounting S1 Study Program. This study uses a quantitative method with a sample of 70 students of the Accounting Study Program FEB UNud. Samples were taken by purposive sampling technique. The data analysis technique in this study used multiple linear regression analysis. The results showed that simultaneously self-motivation, family environment, income expectations, and entrepreneurship education had a positive and significant effect on student interest in entrepreneurship. Partially self-motivation and entrepreneurship education have a positive and significant effect on student interest in entrepreneurship, while family environment and income expectations have a positive but not significant effect on student interest in entrepreneurship. It is expected that the student environment, both from the family and the campus environment, can support students' interest in becoming entrepreneurs so that the interest of S1 Accounting Study Program students in entrepreneurship will increase.